(untitled) (Research, Society and Development, 2021)
The content approach related to Water Microbiology improves the formation of environmental awareness in the student. The use of educational games aims to assist in the teaching-learning process and encourage a connection with the topic addressed. In this context, the objective was to describe the process of building and evaluating a game as a facilitating mechanism for the teaching of Water Microbiology. It is a qualitative and quantitative research, in which a board game was made, evaluated by a questionnaire with specialists, it was also applied to 7th grade classes in two schools in the Metropolitan Region of Fortaleza-CE, being evaluated through the elaboration of descriptive drawings by students. Five experts pointed out improvements, in particular, in the gameplay, coloring and more explicit information in the manual. After the improvements, the game was applied to thirty students and it was found that 79.8% of them are able to perceive everyday problems that are connected to the theme and 53.5% demonstrate it through their lines and colors. Thus, it is concluded that using the didactic game to approach content transversal to the content taught in Elementary School - final years, allows to stimulate interest in the discipline and thus make the student protagonist in his teaching-learning process.